Enhancing Solubility and Dissolution Rate of Antifungal Drug Ketoconazole through Crystal Engineering - Hongmei Yu; Li Zhang; Meiju Liu; Dezhi Yang; Guorong He; Baoxi Zhang; Ningbo Gong; Yang Lu; Guanhua Du (MDPI AG, 2023)
To improve the solubility and dissolution rate of the BCS class II drug ketoconazole, five novel solid forms in 1:1 stoichiometry were obtained upon liquid-assisted grinding, slurry, and slow evaporation methods in the presence of coformers, namely, glutaric, vanillic, 2,6-dihydroxybenzoic, protocatechuic, and 3,5-dinitrobenzoic acids. Single-crystal X-ray diffraction analysis revealed that the hydroxyl/carboxylic acid. . .N-imidazole motif acts as the dominant supramolecular interaction in the obtained solid forms. The solubility of ketoconazole in distilled water significantly increased from 1.2 to 2165.6, 321.6, 139.1, 386.3, and 191.7 μg mL−1 in the synthesized multi-component forms with glutaric, vanillic, 2,6-dihydroxybenzoic, protocatechuic, and 3,5-dinitrobenzoic acid, respectively. In particular, the cocrystal form with glutaric acid showed an 1800-fold solubility increase in water concerning ketoconazole. Our study provides an alternative approach to improve the solubility and modify the release profile of poorly water-soluble drugs such as ketoconazole.